Strategi Pemasaran Jamu Wedang Uwuh di Home Industri Dikafit Kabupaten Sukoharjo - Siti Munawaroh; Tria Rosana Dewi; Irma Wardani (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
The pandemic period impacts the economy in Indonesia, including small and medium enterprises. One of the Micro, Small and Medium Enterprises that can still maintain its existence is the herbal medicine industry. Dikafit is a micro and small business that has been affected by the pandemic, so it needs a strategy to be able to survive. Identifying internal and external factors to determine Dikafit's position and strategic priorities can be applied to the marketing of Dikafit's wedhang uwuh herbs.The basic method used is descriptive qualitative. The research location was determined purposively (intentionally) at Home Industry Dikafit Sukoharjo. The types of data used are primary and secondary data. Data collection techniques by interview, observation, documentation, and literature study. Data analysis methods used are internal and external factors, IFE and EFE matrices, IE matrix, SWOT matrix, and QSPM matrix. The results showed that (1) the internal factor of the main strength was the chemical free product, while for its weakness the distribution area was still limited. The foremost external factor is high consumer loyalty, while the threat is unstable political stability. (2) The resulting alternative strategies (a) maintain prices and improve product quality to increase consumer loyalty, (b) maintain the image of the industry, (c) increase the ability to cope with seasonal changes, (d) provide training and assistance in the form of tools production, (e) seeking and maintaining good relationships with new distributors and suppliers, (f) utilizing government policies to take part and provide training for human resources to better master the broad market and the ability and skills to create products, (g) build and develop with distributors and suppliers to increase production capacity. (3) The priority of the marketing strategy is to build and develop with distributors and suppliers to increase production capacity.